Pengaruh Gaya Kepemimpinan Terhadap Kinerja Karyawan Pada Kantor Jasa Penilai Publik (KJPP) Sih Wiryadi dan Rekan area Samarinda - Didik Permadi, A. (PREDIKSI, 2015)
The purpose of this study was to determine, whether there is a positive and significant influence of leadership style toward employee performance on KJPP Sih Wiryadi and Partners Samarinda. With the above purpose, the analysis tool used in this study is the Product Moment Correlation Coefficient. The results show the significant influence of leadership style on employee performance on KJPP Sih Wiryadi and Partners Samarinda. It based on the calculation results stated r_empiris greater than r_teoretis namely 0.482> 0.413 for the critical value of n = 15 with a significance level of = 0.05. And the terms of the interpretation of the correlation coefficient that the results of these calculations were at the interval coefficient from 0.61 to 0.80 then they have a relationship that was strong enough / close.Based on calculations made to test the hypothesis by using the "t test" contained t_test amounted to 4.575, while that for the prices of critical t_student is 1.714, which means that t_test greater than t_tabel namely 4.575> 1.714 the critical value n - 2 = 15 with a significance level of 0.05, the 95% confidence level. There is significant influence of leadership style toward employee performance KJPP Sih Wiryadi and Partners Samarinda.